DIAGNOSIS AND TREATMENT OF SUDDEN SENSORINEURAL HEARING LOSS: LITERATURE REVIEW AND RESEARCH METHODS - Lutfullaeva G.U. (Central Asian Journal of Medicine, 2025)
A distinguishing feature of sudden sensorineural hearing loss (SSNHL) is a rapid onset of sensorineural hearing impairment occurring within 72 hours, which is almost always unilateral. Most cases are idiopathic, and the degree of hearing loss significantly affects the prognosis for recovery. The aim of this study was to evaluate the effectiveness of steroid and antiviral therapy in the treatment of idiopathic sudden sensorineural hearing loss. We conducted a retrospective study of patients who presented to a tertiary academic specialty medical center. A total of 51 patients were examined. All patients received a standardized treatment regimen. Our treatment protocol resulted in a hearing recovery rate that exceeded the rate of spontaneous recovery. Antiviral therapy and extended steroid treatment duration may contribute to improved recovery outcomes.